Hereditary leiomyomatosis and renal cell cancer (HLRCC): A case report - Yonamine, Tomoko (Urol Case Rep, 2020)
Hereditary leiomyomatosis and renal cell cancer is a rare, inherited disease caused by mutations in the fumarate hydratase gene. It is characterized by cutaneous leiomyomas, uterine leiomyomas, and/or renal cell cancer. We present the case of a 42-year-old woman with a heterozygous missense mutation (p.M195T) in the fumarate hydratase gene. Although the patient did not have cutaneous leiomyoma and she had no family history of hereditary leiomyomatosis and renal cell cancer, the presence of early onset symptomatic uterine leiomyoma and type 2 papillary renal cell cancer confirmed the diagnosis of hereditary leiomyomatosis and renal cell cancer.